Intrauterine phenotype, genetic analysis, and pregnancy follow-up of fetuses with the 16p12.2 microdeletion - Cai, Meiying; Lin, Na; Huang, Hailong; You, Wenqiang; Guo, Nan; Xu, Liangpu (Frontiers in Genetics, 2025)
Reports on the intrauterine phenotype of the 16p12.2 microdeletion are few. A retrospective analysis of the clinical data, genetic testing results, and neonatal prognoses of fetuses with the 16p12.2 microdeletion was conducted to provide a basis for their clinical management. The research participants were pregnant women who underwent prenatal diagnoses between November 2016 and June 2024. Among them, 12,000 cases were selected for karyotype analyses and single-nucleotide polymorphism (SNP) array testing. In the SNP array, 13 out of 12,000 fetuses (0.1%) had the 16p12.2 microdeletion, which included 6 cases of distal deletions and 7 of proximal deletions, involving fragment sizes ranging from 511 to 994 kb. The 16p12.2 distal deletion mainly involves the OTOA gene, whereas the 16p12.2 proximal deletion mainly involves the EEF2K and CDR2 genes. Among the 13 fetuses, five exhibited intrauterine phenotypes, including a small biparietal diameter, head circumference cerebellar dysplasia, corpus callosum dysplasia, small abdominal circumference, mild ventriculomegaly, left ventricular hyperechoic foci, small kidney measurements, nasal bone dysplasia, and polyhydramnios. The inheritance testing of six cases revealed that one case was de novo and five were inherited from the father/mother with normal phenotypes. Except for one case of early abortion, two cases of fetal ultrasound abnormality-led terminations, and one of adverse pregnancy history-based termination, the remaining nine cases included full-term delivery and no significant abnormalities in the birth conditions. One case was lost at follow-up during a phone call 6 months after birth, and the remaining eight infants did not show any significant abnormalities during follow-up. The SNP array effectively diagnosed the 16p12.2 microdeletion, recognized its range and associated genes, and improved the prenatal diagnoses. Thirteen 16p12.2 microdeletion-carrying fetuses lacked intrauterine-specific phenotypes, and eight showed no abnormalities during the most recent postnatal follow-up. However, considering delays in the children’s hearing and neurological development, it is important to conduct continuous and regular post-birth follow-ups. When 16p12.2 deletions are inherited or restricted to distal regions, they often exhibit reduced penetrance. This underscores the need for cautious interpretations of prenatal genetic data.